2010
DOI: 10.1007/s11199-009-9731-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the ABC’s of the Birds and the Bees: What Mothers Teach Young Children About Sexuality and Reproduction

Abstract: Sexuality education is heavily gendered at adolescence. This study uses data from a national web survey of 631 U.S. mothers of 3 to 6 year old children to test whether similar gender differences exist in what mothers teach their young children about sexuality and reproduction. We test (a) whether mothers will report talking more with daughters or sons about sexuality related issues, and (b) whether mothers will report greater comfort talking about such issues with daughters or sons. We find (a) that mothers ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 47 publications
0
35
0
4
Order By: Relevance
“…The finding that mothers are more comfortable engaging with daughters than sons in sex communication also supports the gendered sex communication noted above. This difference in comfort with sex communication based on parents’ gender can be explained in part by a large survey of mothers with young children that found that mothers do not care as much about daughters seeing them naked compared to sons, which provides more early opportunities to talk about bodies and sexuality among mothers and daughters (Martin & Luke, 2010). While seemingly simplistic, these early dyadic exchanges do set a pattern for more mother-daughter discussions that continue through adolescence and beyond.…”
Section: Enduring Sex Communication Issuesmentioning
confidence: 99%
“…The finding that mothers are more comfortable engaging with daughters than sons in sex communication also supports the gendered sex communication noted above. This difference in comfort with sex communication based on parents’ gender can be explained in part by a large survey of mothers with young children that found that mothers do not care as much about daughters seeing them naked compared to sons, which provides more early opportunities to talk about bodies and sexuality among mothers and daughters (Martin & Luke, 2010). While seemingly simplistic, these early dyadic exchanges do set a pattern for more mother-daughter discussions that continue through adolescence and beyond.…”
Section: Enduring Sex Communication Issuesmentioning
confidence: 99%
“…There are key differences in the socialization processes of boys and girls in terms of their sexual behavior; extant studies have found that mothers are more likely to communicate with daughters compared to fathers (Dilorio et al 2000; Hutchinson and Cederbaum 2011; Martin and Luke 2010; Pluhar et al 2008; Wyckoff et al 2008). Additionally, daughters typically report greater comfort and frequency of sex discussions with their mothers (Guzman et al 2003; Kapungu et al 2010).…”
Section: The Significance Of the Maternal Rolementioning
confidence: 99%
“…Mothers are more likely to communicate with daughters (DiIorio et al, 2000; Martin & Luke, 2010; Pluhar et al, 2008; Wyckoff et al, 2008), particularly older daughters (Martino et al, 2008; Pluhar et al, 2008); daughters report greater comfort and frequency of sex discussions with their mothers (Guzman et al, 2003; Kapungu et al, 2010). Mothers more often take primary responsibility for caregiving activities, monitoring (DiClemente et al, 2001), and for discussing sexuality with their children (Hutchinson, 2002).…”
Section: Mother-daughter Communicationmentioning
confidence: 99%